2016
DOI: 10.1007/s00402-015-2388-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effect of unloader braces for medial osteoarthritis of the knee: a systematic review (CRD 42015026136)

Abstract: PurposeThere is a lack of consensus regarding biomechanical effects of unloader braces for the treatment of medial osteoarthritis (OA) of the knee. The purpose of this study was to perform a systematic review of studies examining the biomechanical effect of unloader braces.MethodsA systematic search for articles about the biomechanical effect of unloader braces was performed. Primary outcome measure was the influence of the brace on the knee adduction moment. Data sources were Pubmed central and google scholar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…Emerging studies paid attention to the changes of force lines in knee joint. Unbalance of weight bearing will somehow change the knee force lines and cause lower limb abnormality, leading to progress of KOA [10][11]. Theoretically, the valgus knee bracing can optimize the direction of force line in knee joint, further reducing pain symptoms and improving joint function [12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies paid attention to the changes of force lines in knee joint. Unbalance of weight bearing will somehow change the knee force lines and cause lower limb abnormality, leading to progress of KOA [10][11]. Theoretically, the valgus knee bracing can optimize the direction of force line in knee joint, further reducing pain symptoms and improving joint function [12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Valgus knee bracing is found to effectively correct the lower limb force lines, release pain feelings and improve joint functions of KOA patients by optimizing their biomechanical axis [10][11][12][13]. Kirkley et al [14] showed that valgus knee bracing can effectively reduce the pain symptom and joint mobility of KOA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline scores are associated with improvements in WOMAC scores due to bracing 5 Kinematics and kinetics Related to severity 33 and progression 1,34 of knee osteoarthritis and often used to assess brace performance 35,36…”
Section: Womac Scoresmentioning
confidence: 99%
“…Unloader knee braces have been used in osteoarthritis to modulate mechanical stress on the symptomatic joint compartment [23]; however, there has been a lack of consensus regarding the biomechanical and clinical effects of these devices [24]. Petersen et al [24] performed a systematic review of studies that have examined the biomechanical effect of these braces.…”
Section: Unloader Bracesmentioning
confidence: 99%
“…Petersen et al [24] performed a systematic review of studies that have examined the biomechanical effect of these braces. Twenty of 24 reviewed articles indicated that valgus unloader braces were associated with a significant reduction in the knee adduction moment in patients with osteoarthritis and seven of these articles reported decreased pain in bracetreated patients.…”
Section: Unloader Bracesmentioning
confidence: 99%